Ibn Taymiyyah on the Hadith of the 73 Sects - Abdallah, Ssekamanya Siraje (Afkar: Jurnal Akidah dan Pemikiran Islam, 2006)
The hadith of seventy-three sects has been under stood in various ways by different Muslim scholars. From the early days of Islam, theologians used it as a basis for composing works in which they enumerated the various sects, their leaders, and beliefs. Later, this practice was taken to extremes by some Muslim groups which considered themselves to be the only true Muslims and others to be deviant sectarians and outright infidels. They then would subject them to atrocities and acts of aggression as they wished. Most of the time the hadith in question is used without any attempt to explain its meaning and theological implications. In this paper, a translation of Ibn Taymiyyah's commentary on the hadith of seventy-three sects is presented, preceded by a brief introduction to put it into proper context. The main idea submitted by Ibn Taymiyyah is the necessity of moderation {al-wasat). He warns against summary excommunication of any Muslim groups, as long as they still profess the teachings of Islam.